Counts of chironomid head capsules for the Eemian sediment sequence retrieved from Sokli (Finland) in 2010 - Anna Plikk; Stefan Engels; Maria Fernández-Fernández; Christos Katrantsiotis; Malin E Kylander; Ludvig Löwemark; Sakari Salonen; Minna Väliranta; Karin Helmens (PANGAEA, 2025)
This dataset provides counts of chironomid head capsules for the Eemian sediment sequence retrieved from Sokli (Finland) in 2010. Counts per taxon are presented against both depth (m) and age (ka BP). The chironomid dataset provides information on Eemian lake ecosystem dynamics and was used to quantitatively reconstruct climate conditions (Plikk et al., 2019). A total of 79 samples from the Eemian sediment sequence were treated with warm KOH (10%) to de-flocculate the material and subsequently rinsed through a sieve with a 100-μm mesh. Chironomid head capsules (HCs) were hand-picked from the residue using a Bogorov sorting tray and mounted on permanent microscope slides using Euparal mounting medium. HCs were identified using Brooks et al. (2007). The uppermost three samples (1629–1600 cm) contained only a few chironomids and are excluded from the dataset presented here. Where the sum of head capsules was below 50, neighbouring samples have been amalgamated to ensure a representative count sum was reached. The final dataset presented here contains 73 samples. All analyses were performed in the laboratories of Stockholm University, Sweden.